Agrobacterium-Mediated Transient Transformation of Marchantia Liverworts. (12th August 2021) - Iwakawa, Hidekazu; Melkonian, Katharina; Schlüter, Titus; Jeon, Hyung-Woo; Nishihama, Ryuichi; Motose, Hiroyasu; Nakagami, Hirofumi
Abstract: Agrobacterium -mediated transient gene expression is a rapid and useful approach for characterizing functions of gene products in planta. However, the practicability of the method in the model liverwort Marchantia polymorpha has not yet been thoroughly described. Here we report a simple and robust method for Agrobacterium -mediated transient transformation of Marchantia thalli and its applicability. When thalli of M. polymorpha were co-cultured with Agrobacterium tumefaciens carrying β-glucuronidase ( GUS ) genes, GUS staining was observed primarily in assimilatory filaments and rhizoids. GUS activity was detected 2 days after infection and saturated 3 days after infection. We were able to transiently co-express fluorescently tagged proteins with proper localizations. Furthermore, we demonstrate that our method can be used as a novel pathosystem to study liverwort–bacteria interactions. We also provide evidence that air chambers support bacterial colonization.